Paths to a Future for Youth in Protracted Refugee Situations: A View from the Thai-Burmese Border - Purkey, Mary (Refuge: Canada's Journal on Refugees, 2012)
As youth in protracted refugee situations reach adulthood, the challenges of providing education to them have increased. Along the Thai-Burmese border, some creative approaches are being taken in order to respond to their needs. This article describes four programs, each with a different character. Although available to relatively few, they demonstrate some roles that civil society, and in particular educators and educational institutions, can play in delivering or in ensuring access to higher education for refugee youth living in protracted situations. Most critical are creativity, flexibility, and respectful collaboration betwee neducators and both refugee and host communities.